THE INFLUENCE OF GUIDED DISCOVERY LEARNING MODEL ON BIOLOGY RESULT STUDY AT SMA N 2 SUKOHARJO ACADEMIC YEAR 2013/2014 - Yudi Rinanto, Diana Fatihatul U, Maridi (Pendidikan Biologi, 2015)
The aim of the research is to find out the effect of Guided Discovery Learning on the Biology learning outcome of the students in SMA Negeri 2 Sukoharjo in the school year of 2013/2014.This research employed Quasi-experimental research with Posttest Only with Nonequivalent Control Group Design. The population of research was the even semester XI IPA graders of SMA Negeri 2 Sukoharjo in the school year of 2013/2014. The sample of research was taken using Cluster Sampling. Techniques of collecting data used were test and non-test method. Test method included essay of biological learning outcome in knowledge domain, while the non-test one included observation, questionnaire, and documentation. The hypothesis testing was conducted using t-test with SPSS version 17 help.The result of research showed that H0 was not supported, meaning that there was an effect of the Guided Discovery Learning toward the Biology learning outcome of the students in SMA Negeri 2 Sukoharjo in the school year of 2013/2014. The mean score of biological learning outcome in experiment class was higher than that in control class with the highest mean occurred in attitude domain, and the lowest one occurred in skill domain.Based on result, it could be concluded that Guided Discovery Learning affected the improvement of biological learning outcome in the students of SMA Negeri 2 Sukoharjo in the school year of 2013/2014. Keywords: Guided Discovery Learning, GDL, biological learning outcome.